EVIDENCE BASED CASE REPORT (EBCR): PENGARUH KOMPRES DINGIN TERHADAP PENURUNAN NYERI PERSALINAN KALA I FASE AKTIF (Jurnal Kesehatan Siliwangi, 2022)
Background: Labor and birth are normal physiological events. The last few hours of pregnancy are marked by uterine contractions that cause effacement, dilatation of the cervix and forcing the fetus out through the birth canal. In the active phase of labor, the frequency and duration of uterine contractions increase and the mother feels more and more unbearable pain. One of the non-pharmacological treatment options for labor pain is cold compress therapy. Purpose:  The purpose of this report is to find out whether cold compresses can reduce labor pain in the active phase of the first stage. Method: The article search method uses the Garuda and Google Schoolar databases. The intervention was carried out by applying a cold compress to the mother for 10 minutes and repeated every 30 minutes for 7 sessions. Result: The report results from the assessment of maternal pain using the Numeric Rating Scale (NRS) before and after the intervention showed a significant difference with a decrease of 2 scales. Conclusion: Cold compresses are effective in reducing labor pain.